Analysis of Patient Flows Using Discrete-Event Simulation (Case Study: Emergency Department of Hospital X) - Liperda, Rahmad Inca (Jurnal Logistik Indonesia, 2022)
This research is intended to analyze the patient flows through a number of processes in the Emergency Department (ED) using Discrete Event Simulation (DES) approach. In this paper, the time that a patient spends in the ED as well as the total number of patients served by the ED in a day were investigated and compared with the standard of the medical service time set by the hospital. A case study of Hospital X’s ED in Jakarta, Indonesia was modeled using ProModel software. In addition, this research also proposes a number of considerable scenarios for defining the suitable number of beds and nurses. The results signify that the average time spent in the ED and the number of patients served can be optimized by adding 1 nurse and 2 beds. This finding signifies that the DES modeling approach may assist the hospital managers with the decent decision for improving the efficiency of the patient flows in the ED.